COP9 signalosome: Discovery, conservation,activity, and function - Nanxun Qin (Journal of Integrative Plant Biology, 2020)
The COP9 signalosome (CSN) is a conserved protein complex, typically composed of eight subunits (designated as CSN1 to CSN8) in higher eukaryotes such as plants and animals, but of fewer subunits in some lower eukaryotes such as yeasts. The CSN complex is originally identified in plants from a genetic screen for mutants that mimic light‐induced photomorphogenic development when grown in the dark. The CSN complex regulates the activity of cullin‐RING ligase (CRL) families of E3 ubiquitin ligase complexes, and play critical roles in regulating gene expression, cell proliferation, and cell cycle. This review aims to summarize the discovery, composition, structure, and function of CSN in the regulation of plant development in response to external (light and temperature) and internal cues (phytohormones).